Study of the expression of a Small Leucin-Rich Proteoglycan, Asporin, in normal human osteoblasts and regulation by breast cancer cells - Trombino, Giovanna Elvi; Sisci, Diego; Bellahcène, Akeila; Lanzino, Marilena (My University, 2014)
Asporin (ASPN) is an extracellular matrix protein that belongs to the Small Leucine Rich Repeat proteoglycan (SLRP) family. Asporin is abundantly expressed in the articular cartilage of individuals with osteoarthritis. In the context of osteoarthritis, several studies have shown that asporin regulates cartilage matrix gene expression and cartilage formation by modulating the transforming growth factor-β (TGF- β) signaling pathway. Asporin directly binds to TGF‐β and inhibits TGF-β-mediated expression of cartilage matrix genes. Previous studies in our laboratory, showed that Asporin inhibits TGF- β-1-mediated SMAD2 phosphorylation in breast cancer cells as well as migration and epithelial to mesenchymal transition in A549 human lung cancer cells. The present study was undertaken to investigate whether asporin secretion could indirectly mediate the ability of metastatic breast cancer cells to regulate osteoblastic differentiation. The Wnt antagonist sclerostin (SOST) is a potent inhibitor of bone formation. We considered the possibility that the balance between ASPN and SOST present in the ECM may create a specific environment favorable to aggressive breast cancer cell growth. Results: Breast cancer cells do not produce ASPN themselves but they regulate its expression in osteoblasts. Normal human osteoblasts have been cultured in presence of MCF7 and MDA-MB-231 serum-free conditioned medium. Immunoblot analysis and real time PCR, revealed a significant increase in ASPN expression and secretion in osteoblasts treated with MCF7-conditioned medium, while the opposite effect was observed with MDA-MB-231-conditioned medium. We investigated the role of MCF7 and MDAMB231 conditioned media in osteoblast differentiation and mineralization through alkaline phospatase and Runx2 expression. Our results showed the ability of MCF7 conditioned medium to induce the osteoblast differentiation and mineralization compared to the MDA-MB-231 conditioned medium treatment. Osteoblasts treated with MCF7 conditioned medium and challenged with recombinant SOST showed a significant reduction in their differentiation potential through the decrease of ASPN expression. Contrarily to non-metastatic MCF-7 breast cancer cells, MDA-MB-231 metastatic breast cancer cells inhibited the secretion of ASPN by osteoblasts through the overexpression of SOST. The result is the reduction of osteoblast differentiation and mineralization that can create a specific environment favorable to aggressive breast cancer cell growth
Dottorato di Ricerca in Biochimica Cellulare ed attività dei Farmaci in Oncologia, Ciclo XXVII, a.a. 2014
Keywords: Biochimica; Tumori; Mammella